Application of a novel strong promoter from Chinese fir (Cunninghamia lanceolate) in the CRISPR/Cas mediated genome editing of its protoplasts and transgenesis of rice and poplar - Ye, Shanwen; Ding, Wensha; Bai, Weiyuan; Lu, Jiaao; Zhou, Linying; Ma, Xiangqing; Zhu, Qiang (Frontiers in Plant Science, 2023)
Novel constitutive promoters are essential for plant biotechnology. Although in angiosperms, a number of promoters were applied in monocots or dicots genetic engineering, only a few promoters were used in gymnosperm. Here we identified two strong promoters (Cula11 and Cula08) from Chinese fir (C. lanceolate) by screening the transcriptomic data and preliminary promoter activity assays in tobacco. By using the newly established Chinese fir protoplast transient expression technology that enables in vivo molecular biology studies in its homologous system, we compared the activities of Cula11 and Cula08 with that of the commonly used promoters in genetic engineering of monocots or dicots, such as CaM35S, CmYLCV, and ZmUbi, and our results revealed that Cula11 and Cula08 promoters have stronger activities in Chinese fir protoplasts. Furthermore, the vector containing Cas gene driven by Cula11 promoter and sgRNA driven by the newly isolated CulaU6b polyIII promoters were introduced into Chinese fir protoplasts, and CRISPR/Cas mediated gene knock-out event was successfully achieved. More importantly, compared with the commonly used promoters in the genetic engineering in angiosperms, Cula11 promoter has much stronger activity than CaM35S promoter in transgenic poplar, and ZmUbi promoter in transgenic rice, respectively, indicating its potential application in poplar and rice genetic engineering. Overall, the novel putative constitutive gene promoters reported here will have great potential application in gymnosperm and angiosperm biotechnology, and the transient gene expression system established here will serve as a useful tool for the molecular and genetic analyses of Chinese fir genes.